Bezirk Charkiw, Ukraine. Die Infrastruktur im Gebiet der Dnepr-Severskij Donec-Wasserscheide in spätrömischer Zeit und zu Beginn der Völkerwanderungszeit. Die Arbeiten des Jahres 2019 - Schultze, Erdmute (e-Forschungsberichte des DAI, 2020)
The joint project including scientists from the Ukraine and Germany was attended to several focus points. One of them was the settlement history of the 4th and 5th century AD in the vicinity of Voitenki. The surveys of previous years in this area have been analysed. Further investigations were focused on the sites near Perekop, where at least one huge settlement of the Chernyakhov culture is known by finds from the surface. For preparing detailed investigations a quadrocopter recorded the site and a survey offered first data for soil science. The excavations in Voitenki confirmed that the settlement was extended on both sides of a water-course. In part D a sunken floor building was discovered dating to the second half of the 3rd century, the horizon before the dissemination of the Chernyakhov culture. Excavations on the cemetery brought to light grave 233–240. The high number of excavated burials offers the opportunity for special investigations concerning the social structure of the Chernyakhov culture. Therefore another focus point of the project is devoted to this cemetery. In cooperation with anthropologists the ongoing analyses is focused on the burial rites and the evidences for the social structure of the buried community.